Pengembangan Biskuit Daun Kelor (Moringa oleifera) Yang Diperkaya Tulang Ikan Tuna (Thunnus Sp) Sebagai Makanan Tambahan Tinggi Kalsium: Development of Moringa Leaf (Moringa oleifera) Biscuit Enriched with Tuna (Thunnus Sp) Bones as an Additional Food High in Calcium - Avicena, Rasyid; Syahrial; Purnakarya, Idral (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2024)
The use of tuna fish is still focused only on the flesh, the rest, such as tuna bones, only become waste, both at the industrial level and at the household level because its use has not been carried out optimally, even though fish bones contain tricalcium phosphate compounds which for the human body have ideal benefits. This study aims to develop a biskuit product made form moringa oleifera leaf flour enriched with tuna fish bone meal (Thunnus Sp) as a supplementary food for premenopausal women. The type of research is experimental using a Complately Randomize Design (CRD). Direct experimental were carried out on the addition of tuna bone meal to the moringa leaf flour biskuit product with 4 treathment namely 0 gr (F0), 20 gr (F1), 40 gr (F2), and 60 gr (F3) with 2 repetitions. The results showed that the selected formula of moringa leaf flour biscuit with tuna bone meal based on hedonic test, hedonic quality and nutritional test was F1 with the likes and the characteristics of a slightly light color, slightly fragrant aroma, slightly sweet test, and crunchy texture. The nutritional content of the selected formula is 13,2% water content, 3,4% ash content, 9,25% protein, and 1.398,223 mg calcium. The selected formula for the development of moringa leaf flour biscuit enriched with tuna bone meal is F1 with the addition of 10% tuna bone meal or 20 grams.